2019
DOI: 10.3390/soc9010015
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and Work-Related Stress in the Irish Workplace

Abstract: Work-related stress is increasing in prevalence, with important consequences for employees, employers, the economy, and wider society. While previous research has identified a link between work-related stress and bullying, gaps remain in our understanding of the nature of the relationship. This article uses ordered logistic regression and nationally representative data on 5110 employees from Ireland to empirically analyse the distribution of subjective work-related stress and its relationship with bullying (se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…It has been argued that larger organisations are more likely to have systems and processes in place to tackle bullying and associated ill-treatment (O’Connell et al, 2007). Similarly, while the existence of anti-bullying or dignity at work policies is associated with lower stress levels for employees (Baillien et al, 2011a; Cullinan et al, 2019) questions about the preparedness of SMEs to tackle adverse social behaviours at work remain. Thus, our study is able to contribute to the debate but focusses on medium-sized firms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been argued that larger organisations are more likely to have systems and processes in place to tackle bullying and associated ill-treatment (O’Connell et al, 2007). Similarly, while the existence of anti-bullying or dignity at work policies is associated with lower stress levels for employees (Baillien et al, 2011a; Cullinan et al, 2019) questions about the preparedness of SMEs to tackle adverse social behaviours at work remain. Thus, our study is able to contribute to the debate but focusses on medium-sized firms.…”
Section: Discussionmentioning
confidence: 99%
“…In the face of poor levels of leadership/management support, it is not unreasonable for employees in SMEs to seek co-worker support, particularly in the smallest of firms where employees and owner-managers work in close proximity. While Cullinan et al (2019) found no evidence in Ireland for the effects of co-worker support on stress levels, others such as Lewis et al (2017) reported their importance in buffering the effects of bullying and harassment in SMEs. Fevre et al (2012) capture these concepts using the FARE acronym representing fairness and respect (see also Walker and Fincham, 2011).…”
Section: The Paradox Of Smesmentioning
confidence: 94%
See 2 more Smart Citations
“…Workplace bullying is a pervasive problem with significant personal, social and economic costs. These include important deleterious effects on both physical and mental health, which can range from stress and unpleasant but manageable anxiety, to post traumatic stress disorder [1][2][3]. Other personal effects include poor concentration, increased propensity to accidents, lowered commitment and performance, increased consumption of alcohol and increased strain on personal relationships [4].…”
Section: Introductionmentioning
confidence: 99%